Tables for the calculation of friction in internal flows - Barr, D. I. H. (Thomas Telford, 1995)
This system of tables derives from that adopted in Volume II of the 6th edition of the 'Wallingford Table'. In providing table-based aid for solution of the Colebrook-White equation, it extends to variation in kinematic viscosity, the incremental approach, a feature of the Wallingford Tables.